The dynamic effects of religion: An exploration of religiosity influences on Islamic work ethic over time - Jaya Addin Linando; Yunice Karina Tumewang; Katiya Nahda; Nurfauziah (Cogent Business & Management, 2023)
AbstractAs a country with the biggest Muslim population in the world, Indonesia is a fascinating avenue to conduct studies about Muslim behavior, including in the workplace context. The present study focuses on exploring religiosity’s effect on Islamic work ethic (IWE). Using the 5th and the 7th waves of World Values Survey (WVS) data, in total this study processes 2474 Indonesian Muslim respondents’ data. Among the notable findings is that religiosity has a dynamic effect on IWE. Religiosity is found to positively and significantly influence IWE in the 5th wave (2006) but the significant influence is no longer found in the 7th wave (2018). The authors argue that globalization, secularism, and the new way Muslims learn their religion may be the source of these dynamics. While religiosity does not influence IWE in contemporary times, the authors propose national culture and macroeconomic factors as the prospective factors driving individuals’ IWE. The present study is arguably among the first studies to comprehensively explore IWE as a multidimensional construct, involving both micro (individual-as being represented by religiosity) and macro (societal) perspectives to bring about IWE’s discourses. Additionally, the time-series data this study employed also offer a rich discussion on how religiosity influences (or does not influence) individuals’ IWE.